CASE REPORT: TREATMENT OF RIGHT EYEBALL PROLAPSE IN A DOMESTIC KITTEN USING TRANSCONJUNCTIVAL ENUCLEATION APPROACH - Ni Luh Kadek Ratih Jusniari; I Gusti Ngurah Sudisma; I Wayan Gorda (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Prolapse of the eyeball refers to the protrusion of the globe from the orbital cavity and may be caused by various factors, including infection, increased intraocular pressure, trauma, and abnormalities of the extraocular muscles. A three-month-old female domestic cat weighing 0.9 kg presented with prolapse of the right eyeball. The cat was treated surgically using a transconjunctival enucleation approach. This procedure was selected because the ocular abnormalities could not be resolved through medical therapy. Prior to surgery, premedication with atropine sulphate (0.03 mg/kg BW) was administered subcutaneously. Fifteen minutes later, anesthesia was induced and maintained by intramuscular injection of a combination of ketamine (11 mg/kg BW) and xylazine (2 mg/kg BW). Postoperatively, the animal received antibiotic therapy with cefotaxime (20 mg/kg BW, q12h, intramuscularly) and anti-inflammatory treatment with meloxicam (0.2 mg/kg BW, q24h, subcutaneously). This was followed by oral administration of cefixime (10 mg/kg BW, q12h) and meloxicam (0.1 mg/kg BW, q24h) for five days, along with supportive therapy using Fufang E’jiao Jiang® (0.5 mL/kg BW, q24h, per oral). Based on wound observations up to the seventh postoperative day, the surgical incision had not completely dried; however, the wound healing process progressed well, and no signs of infection were observed at the surgical site.